A CROSS-SECTIONAL STUDY ON CORRELATION BETWEEN SERUM URIC ACID LEVEL AND CAROTID ATHEROSCLEROSIS IN PATIENTS OF TYPE 2 DIABETES - RAJPOOT, SURJEET SINGH; GUPTA, RUPESH KUMAR; AGARWAL, GAURAV; SARAL, SWATI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to assess correlation between uric acid (UA) level and carotid intima media thickness (CIMT) in type 2 diabetes mellitus (DM) patients. Methods: The study was conducted in the Department of Medicine, SMS Medical College and Attached Hospital, among adults with type 2 DM. It was cross-sectional study conducted from April 1, 2019, to December 31, 2020. Sample size is calculated 60 patients of Type 2 DM. As per previous study show correlation coefficient between serum UA (SUA) level and CIMT (r=0.779)52 (For 90% power and 1% α error). CIMT and carotid artery plaques were measured through Doppler ultrasound. The thickness was measured at 1 cm proximal to the dilatation of the carotid bulb. The mean of maximum IMT of both the common carotid artery is taken as the average CIMT. Results: Most patients (60%) were diabetics since 5 years and nearly 30% had diabetes since 5–15 years while only 10% had diabetes since more than 15 years. Mean duration of diabetes was 6.91±5.88 years. Two thirds of diabetic individuals (67%) had HDL cholesterol level above 40 mg/dL. About 42% of diabetic individuals had triglyceride level <150 mg/dL and 5% of diabetic individuals had LDL cholesterol level <100 mg/dL. Mean HDL cholesterol, Triglycerides, and LDL cholesterol were 47.4±15.49 mg/dL, 153.78±81.56 mg/dL, and 92.33±57.28 mg/dL, respectively. Mean bilirubin and serum creatinine in study population were 0.65±0.48 mg/dL and 0.96±0.18 mg/dL, respectively. Mean CRP was 3.95±2.40 mg/L. Mean SUA level in study population was 5.78±2.18 mg/dL. Mean of average CIMT was found to be 8.0±1.16 mm. Glycated hemoglobin (HbA1c) and UA had negative weak linear correlation which was statistically significant. HbA1c and average CIMT had no or week negative correlation which was not statistically significant and SUA and average CIMT showed positive moderate linear correlation which was statistically significant. Conclusion: Carotid atherosclerosis as measured by IMT is associated with SUA levels in patients with type 2 DM. In type 2 DM patients, HbA1C is negatively correlated with UA while HbA1C has no correlation with CIMT.